A Study On Faculty Promotion Methods In Universities And Research Centers -analyticalstudy Of Promotion Regulations And Conditions In Maghreb Universities – - Fakhari Farouk; Zebiri Noura (جامعة الوادي University of Eloued, 2024)
This research endeavors to elucidate the procedures associated with university promotions within the context of Maghreb universities. Given that the promotion process is intrinsic to the rights of the researching professor, its implications are far-reaching, contributing both directly and indirectly to the enhancement of university faculty performance and the elevation of teaching standards. Through a comprehensive examination and exploration of diverse promotion mechanisms across several Maghreb countries, this study unveils a spectrum of outcomes. Foremost among these findings is the notable disparity in promotion techniques and strategies adopted by different universities. This discrepancy can be attributed to the distinct professional environments in which faculty members operate, as well as the varying legislative frameworks governing this intricate process.
Keywords: Promotion; University; Faculty member; Maghreb universities